PENGEMBANGAN LKPD BERBASIS PROBLEM BASED LEARNING UNTUK MELATIH KEMAMPUAN KONEKSI MATEMATIS PESERTA DIDIK KELAS XI - Tito Nurdiyanto; Inda Rafida; Aulia Nuhadila; Sesi Winarni (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2020)
This study was intended to produce a learner worksheet based on problem based learning with valid and practical, and to determine the potential effects on students mathematical connections ability in derivative material. This is development research type of formative research. The subjects of this research were students of class XI MIPA 1 SMAN 2 Palembang as many as 36 students. Data collection techniques used are interviews, document analysis, and test. The result of document and data analysis could be concluded that this research procuded worksheet based on problem based learning in derivative material valid and practical, and LKPD that had been developed had a potential effect on on students mathematical connections ability in derivative material. Therefore worksheet that had been developed can be used by the students.